Stability and suitability of genotypes and environment to Ascochyta blight of chickpea - Sharma, Mamta; Sharath Chandran, U. S.; Rani, Upasana; Singh, Sudhir K.; Basandrai, Ashwani K.; Basandrai, Daisy (Frontiers in Plant Science, 2023)
Ascochyta blight (AB) is a major biotic constraint to chickpea production internationally. The disease caused by the phytopathogenic fungus Ascochyta rabiei is highly favored by prolonged spells of low temperature and high humidity. The disease scenario is expected to aggravate in the near future as a result of rapidly changing climatic conditions and the emergence of fungicide-resistant pathogen strains. Tapping into host-plant resistance is the most logical way to preempt such a crisis. Presently, high levels of stable resistance against AB are yet to be identified from the chickpea gene pool. The present study was aimed at facilitating this process through multi-environment testing of chickpea genotypes. Using the GGE biplot analysis method, we could identify three genotypes viz. ICCV 16508, ICCV 16513, and ICCV 16516 from the International Ascochyta Blight Nursery, that showed consistent moderate resistance reactions across all the tested environments. Moreover, we were able to evaluate the test locations for their suitability to support AB screening trials. Ludhiana and Palampur locations were identified as the most ideal for continual screening in the future. Controlled environment screening at the ICRISAT location offered to reduce large plant populations to small meaningful sizes through initial screening under controlled environment conditions. This study will further improve the scope of phenotyping and sources of stable resistance to be utilized in future AB resistance breeding programs.